Devil's claw (Harpagophytum procumbens) ameliorates the neurobehavioral changes and neurotoxicity in female rats exposed to arsenic - Rupasree Peruru; R. Usha Rani; Jhansyrani Thatiparthi; Sunitha Sampathi; Sujatha Dodoala; K.V.S.R.G. Prasad (Heliyon, 2020)
Over 200 million people are exposed to arsenic worldwide in their daily lives. Arsenic is a toxic ubiquitous metalloid distributed in the ground water. From the last few decades it is obtaining considerable attention for its severe neurotoxic properties. In this study the neuroprotective efficacy of devil's claw (DCW), a potent antioxidant has been investigated against arsenic induced neurotoxicity in female rats. Neurotoxicity was established by oral administration of 13 mg/kg sodium arsenite. The animals were divided into five groups (n = 6) including normal control, disease/arsenic control, standard treatment (Apocynin, 10 mg/kg), DCW treatment I (DCW, 200 mg/kg) and DCW treatment II (DCW, 400 mg/kg). Exploratory, anxiety and motor coordination related behavior of the animals was assessed using hole-board, forced swimming, beam walk and elevated plus maze tests. Findings revealed that DCW treatment ameliorated anxiety and motor in-coordination in the rats compared to the arsenic control group. In addition, arsenic induced a significant oxidative stress in arsenic only treated group, whereas co-administration with DCW the oxidative stress was reduced prominently. Arsenic control group produced gliosis and nuclear pyknosis of the brain cells which were prominently suppressed with the treatment of DCW for 21 days. The activity of DCW was in correlation with the concentration of harpagoside in the serum estimated by the HPLC method, supports that harpagoside was the active constituent responsible for neuroprotective effect. Further findings are required to understand the molecular mechanisms involved in neuroprotective effect of harpagoside and DCW.